PARLIAMENTARY IMMUNITY, ABUSE OF POWER AND MISINFORMATION: CHALLENGES FACING THE ELECTORAL PROSECUTOR'S OFFICE IN DIGITAL ELECTION CAMPAIGNS (CIPEEX, 2025)
This article will discuss the issue of electoral activity and parliamentary immunity when considering the illegal practice of spreading fake news in the digital environment during political campaigns, as well as the challenges faced by the Electoral Public Prosecutor's Office (MPE) during this period. Within the scope of democratic and legal ethics, and within the limits of the proposed theme, electoral campaigns and the resulting misinformation arising from the dissemination of false information and the abuse of political power by a large majority of candidates are interconnected. The aim is to identify possible criminal offenses in the virtual sphere that are often justified by the immunity of parliamentarians and the prejudice of action and accountability on the part of the MPE. The primary objective remains firm: to analyze how the MPE should act to preserve electoral legality and ensure that immunity is not used to cover up illegal practices, especially in the digital context, proposing strategies to strengthen its role in protecting the integrity of democratic elections. The research contained herein has substantial implications for the electoral sector and also for the formulation of public policies aimed at promoting voters' access to information for informed decision-making, with a view to the full exercise of citizenship and the strengthening of democracy. The methodology adopted is bibliographic research, which, according to Severino (2007), provides researchers with access to writings related to the chosen topic, facilitating the analysis of information that, when debated, stimulates new research.
Keywords: Parliamentary immunity; Misinformation; Election Campaings; Digital Media